2017
DOI: 10.1002/bit.26304
|View full text |Cite
|
Sign up to set email alerts
|

Creating homogenous strain distribution within 3D cell‐encapsulated constructs using a simple and cost‐effective uniaxial tensile bioreactor: Design and validation study

Abstract: Mechanical loading bioreactors capable of applying uniaxial tensile strains are emerging to be a valuable tool to investigate physiologically relevant cellular signaling pathways and biochemical expression. In this study, we have introduced a simple and cost-effective uniaxial tensile strain bioreactor for the application of precise and homogenous uniaxial strains to 3D cell-encapsulated collagen constructs at physiological loading strains (0-12%) and frequencies (0.01-1 Hz). The bioreactor employs silicone-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The SEM images of loaded ASC-encapsulated scaffolds showed distinct compaction of collagen fibers at each of the applied strains and frequencies, while the nonloaded control group exhibited a highly random matrix (Figures 2(a) and 3(a) ). Our previous study demonstrated that even on applying the same uniaxial tensile loading regime, the extent of collagen matrix compaction can vary significantly based on the type of cells encapsulated within the scaffold [ 28 ]. Also, higher cell densities within the scaffold are known to increase the extent of matrix compaction and increase the diameter of collagen fibers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEM images of loaded ASC-encapsulated scaffolds showed distinct compaction of collagen fibers at each of the applied strains and frequencies, while the nonloaded control group exhibited a highly random matrix (Figures 2(a) and 3(a) ). Our previous study demonstrated that even on applying the same uniaxial tensile loading regime, the extent of collagen matrix compaction can vary significantly based on the type of cells encapsulated within the scaffold [ 28 ]. Also, higher cell densities within the scaffold are known to increase the extent of matrix compaction and increase the diameter of collagen fibers [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, ASCs (passage 4) were encapsulated at 750,000 cells/ml seeding density within 3 mg/ml collagen I solution and neutralized to pH 7~8 with chilled 1 N NaOH solution along with PBS and cell culture media according to the manufacturer's instructions. The cell-collagen solutions were added into the loading chambers of our custom-built uniaxial tensile strain bioreactor [ 28 ] and polymerized at 37°C for 1 hour. Then, 3D cell-encapsulated collagen scaffolds were incubated in the culture media for 48 hours in a standard cell culture incubator at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of these physical stimuli into molecular signals and biological responses, which is referred to as mechanotransduction, drives molecular cascades of events triggering bone remodelling 3,4 . Accordingly, an appropriate mechanical loading of cells in culture promotes their expansion 5 , along with mineralized extracellular matrix (ECM) production 68 . Cell physical triggering can be obtained via dedicated actuators - usually referred to as bioreactor systems - addressing a specific tissue phenotype according to their setup configuration 917 .…”
Section: Introductionmentioning
confidence: 99%
“…To better distribute seeded cells onto scaffolds, others described the application of mechanical stimuli in the absence of a fluid perfusion. 1,17,18,26 Moreover, a mechanical stimulation mimicking physiological loads improves the cellular production of collagen, and fiber orientation while preserving biomechanical properties of the tendon-derived scaffolds. 25 However, to the best of our knowledge, none of the custom-made or commercial bioreactors allows a simultaneous pump-free fluid perfusion and an individual, custom mechanical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another advantage of the OSPB was the possibility to independently stimulate each chamber containing a single construct, differently from other devices that can lodge independent samples, but apply the same stimulation patterns simultaneously. 1,14,17,18 According to this approach, the OSPB advantaged both the experimental in vitro studies and the potential clinical translatability. Indeed, OSPB operates on every single construct and employs different stimulation protocols and harvesting/control time points independently, within the same experiment.…”
Section: Discussionmentioning
confidence: 99%